2008
DOI: 10.1016/j.biomaterials.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of human umbilical vein scaffolds derived from cesarean section vs. vaginal delivery for vascular tissue engineering

Abstract: Umbilical vein function and birth mode Abstra ctThe current study investigated whether the mode of delivery and the mode of sample collection affect the functional properties of umbilical veins as scaffolds for vascular tissue engineering purposes. HUV from planned c-sections (PCS) showed a 1.7-fold higher maximum contraction with potassium chloride compared to spontaneous vaginal deliveries (VD, p=0.029). The maximum contractions with histamine were 2.0-fold and 2.9-fold higher in the PCS and emergency c-sect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…HUV were found to contract to sero tonin and to U46619, to possess a biphasic stress-strain rela tionship [6], to retain part of the contractile function and of tissue viability after cryopreservation, and to release the an tithrombotic agent prostacyclin even after denuding. Vascu lar function and antithrombotic properties were best in HUV from cesarean sections [7].…”
Section: Introductionmentioning
confidence: 93%
“…HUV were found to contract to sero tonin and to U46619, to possess a biphasic stress-strain rela tionship [6], to retain part of the contractile function and of tissue viability after cryopreservation, and to release the an tithrombotic agent prostacyclin even after denuding. Vascu lar function and antithrombotic properties were best in HUV from cesarean sections [7].…”
Section: Introductionmentioning
confidence: 93%
“…Die Besiedelbarkeit dieses Materials mit vaskulären Zellen wurde gezeigt. Auch die Umbilikalarterie wurde auf ihre Eignung für das vaskuläre Tissue Engineering untersucht [ 35 , 36 ] Um nach Möglichkeit die optimale Auswahl bei den Nabelschnü-ren für Tissue-Engineering-Anwendungen zu treff en, wurde untersucht, ob der Geburtsmodus einen Einfl uss auf die Umbilikalvenenfunktion hat [ 39 ] . Die Nabelschnüre wurden hierbei in 3 Gruppen unterteilt: (1) vaginale Geburten sowie (2) Literatur…”
Section: Gefäßeunclassified
“…We have previously investigated human umbilical veins (HUVs) as a source for TEBV and demonstrated that endothelium‐denuded HUVs can be seeded with autologous cells from CABG patients to form a confluent and flow‐resistant neoendothelium (Hoenicka et al ., , , ). The present study was undertaken to investigate the utility of decellularized HUV as scaffolds for vascular tissue engineering and to compare these two approaches.…”
Section: Introductionmentioning
confidence: 99%